DISRUPSI VISUAL SEBAGAI STRATEGI BRANDING INKLUSIF IKLAN MS GLOW FOR MEN - Yudianto, Robert Hendra; Setyoko, Adnan; Kusuma, Alfiandi Eka; Ramadhan, Gilang (ASKARA: Jurnal Seni dan Desain, 2025)
This study aims to analyze the strategy of visual disruption in the MS Glow for Men advertising campaign featuring Babe Cabita and Marshel Widianto as the main figures. This visual approach is understood as a reversal of conventional aesthetic norms in male skincare advertisements, which typically showcase idealized figures with fair skin, athletic bodies, and traditionally masculine appearances. Employing Norman Fairclough's Critical Discourse Analysis and Stuart Hall’s theory of representation, the study examines the visual text across three levels: textual analysis, discursive practice, and socio-cultural practice. The results indicate that MS Glow adopts visual disruption not merely as an aesthetic choice, but as an ideological effort to construct a new, more inclusive representation of masculinity. The use of comedic public figures who deviate from standard beauty norms becomes a powerful tool to create emotional connection, digital virality, and participatory discourse. This visual strategy reflects a conscious branding tactic aligned with social transformation and the dynamics of digital media culture. The study contributes to expanding visual communication studies, gender representation, and branding practices in contemporary digital and creative industries